Investigation of Antibacterial and Anti-Diarrhoeal Activities of 80% Methanol Leaf and Fruit Extract of Leonotis Ocymifolia (Burm. F) Iwarsson (Lamiaceae) [Retraction] - Mengie Ayele T; Chekol Abebe E; Bogale Kassie A (Dove Medical Press, 2022)
Mengie Ayele T, Chekol Abebe E, Bogale Kassie A. J Exp Pharmacol. 2021;13:613–626. The Editor and Publisher of Journal of Experimental Pharmacology wish to retract the published article. Following publication, concerns were raised that the results reported in Tables 1, 2, 3, 4 and 5 were identical to results reported in corresponding tables from the master’s thesis of the third author. However, where the reported study investigated antibacterial and anti-diarrhoeal activities from extracts of Leonotis ocymifolia, the thesis reported anti-diarrhoeal activities from extracts of Calpurnia aurea. The authors responded to our queries but were unable to provide a satisfactory explanation for how the results reported in both articles were identical. The Editor determined the reported findings were unreliable and requested for the article to be retracted. Our decision-making was informed by our policy on publishing ethics and integrity and the COPE guidelines on retraction. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”. This retraction relates to this paper